Enumeration of Hoya species in Mindanao Island, Philippines: Conservation concerns - REN DIVIEN R. OBENA; INOCENCIO Jr E BUOT (Society for Indonesian Biodiversity, 2019)
Abstract. Obeña RDR, Buot JrIE. 2019. Enumeration of Hoya species in Mindanao Island, Philippines: Conservation concerns. Biodiversitas 20: 1699-1707.  Unknown resources are difficult to utilize. Hence, an extensive study of literature was carried out to determine the Hoya species found in Mindanao, Philippines. The main purpose of the study was to know the Hoya resources in Mindanao, an area which is not exempted to extensive forest degradation. Many of these Hoya species are endemic and vulnerable to extinction. A total of 33 Hoya species which are epiphytes on trees had been recorded in Mindanao. Three species in the area were classified as endangered based on the Department of Environment and Natural Resources (DENR) list of threatened species (DAO 2007-01), while one species is classified as vulnerable based on DAO 2017-11. For the past years, forest cover in the Philippines has been continuously declining. This scenario can negatively affect the population of Hoya since the forest serves as a habitat for these species. Protection of the forest land in Mindanao can serve as a conservation strategy of the Hoya species.